RAMLILA TRADITION AND RAM IN EVERY HEART: A LIVING HERITAGE OF INDIAN CULTURE - Dr. Ravindra Mishra Katyayan; Associate Professor; HOD Hindi (Fakultas Dharma Duta UHN IGB Sugriwa Denpasar, 2025)
Ramlila, the theatrical enactment of the Ramayana, represents one of the most profound and dynamic expressions of India's cultural and spiritual legacy. As a community-centered performance tradition, it serves as both religious devotion and social pedagogy. This paper explores the origins, diverse forms, and evolving cultural role of Ramlila, focusing in particular on iconic performances such as those in Ramnagar (Kashi), Ayodhya, Bissau (Rajasthan), Aishbagh Lucknow, and Delhi. Drawing upon historical records, ethnographic insights, and UNESCO recognitions, the paper discusses Ramlila as an intangible cultural heritage that continues to shape identity, morality, and unity. Special attention is given to the character of Ram as Maryada Purushottam and his symbolic presence in the hearts of devotees, across India and Southeast Asia. By blending scholarly analysis with data from Hindi-language fieldwork and regional sources, this study reaffirms Ramlila's relevance in a rapidly globalizing world.